On Optimal Resource Allocation for Hybrid VLC/RF Networks with Common Backhaul - Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Sofotasios, Paschalis C.; Muhaidat, Sami; Karagiannidis, George K. (IEEE Transactions on Cognitive Communications and Networking, 2020)
The synergy between visible light communication (VLC) and radio frequency (RF) networks has attracted a considerable amount of attention due to the envisioned improvements compared to conventional systems, mainly in terms of data rate and coverage. In this paper, we investigate for the first time the coexistence of VLC and RF networks, assuming that both networks are served by a common backhaul network, as well as both perfect and imperfect channel state information (CSI). In this context, we propose an optimal resource allocation scheme that maximizes the corresponding data rate, while also taking into account the fairness among the involved users. This is of paramount importance because in such heterogeneous networks, a standard rate maximization approach yields a severely degraded performance for the weaker users. In order to provide a tractable solution to the formulated problem, which is non-convex, we transform this into an equivalent convex one. Moreover, a simplified power allocation problem is solved, which provides comparable results with substantially lower complexity. Finally, extensive simulations illustrate the validity and effectiveness of the proposed analysis, and provide valuable insights on the impact of the imperfect CSI on the overall network performance.
Created from Fastlane, Scopus look-up
Keywords: backhaul network; convex optimization; energy efficiency; hybrid VLC/RF; imperfect CSI; resource allocation; Visible light communications